2016
DOI: 10.48550/arxiv.1607.00403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microscopic theory of the Coulomb based exchange coupling in magnetic tunnel junctions

O. G. Udalov,
I. S. Beloborodov

Abstract: We study interlayer exchange coupling based on the many-body Coulomb interaction between conduction electrons in magnetic tunnel junction. This mechanism complements the known interaction between magnetic layers based on virtual electron hopping (or spin currents). We find that these two mechanisms have different behavior on system parameters. The Coulomb based coupling may exceed the hopping based exchange. We show that the Coulomb based exchange interaction, in contrast to the hopping based coupling, depends… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Recently the exchange interaction between magnetic grains was considered using the Hamiltonian Ĥ0 + ĤdC [27]. However, later it was shown [31] that the indirect Coulomb interaction may also lead to magnetic coupling between the FM contacts. In particular, this was demonstrated for MTJ with infinite leads.…”
Section: The Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently the exchange interaction between magnetic grains was considered using the Hamiltonian Ĥ0 + ĤdC [27]. However, later it was shown [31] that the indirect Coulomb interaction may also lead to magnetic coupling between the FM contacts. In particular, this was demonstrated for MTJ with infinite leads.…”
Section: The Modelmentioning
confidence: 99%
“…The Coulomb based exchange coupling between infinite magnetic leads was considered in Ref. [31], where it was shown that the Coulomb interaction inside the FM leads also contributes to the total interlayer exchange coupling. However, for infinite leads the last three terms in Eq.…”
Section: Coulomb Based Exchange Interactionmentioning
confidence: 99%
See 3 more Smart Citations